2019
DOI: 10.1055/s-0039-1679882
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral Thigh Flap in a Chicken Model: A Novel Perforator Training Model

Abstract: Background Preclinical training in perforator flap harvesting is typically conducted on living animal models; however, repeated training is not possible with these models because of ethical and/or economical constraints. We describe an anterolateral thigh flap (ALT flap) training model using chicken thigh that seems to be an appropriate training model prior, for example, to raise a perforator flap in a living rat or swine model. Methods A total of 10 chicken legs were used in this study. Six chicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…11 Innovative training models have been created in many areas of microsurgery from microsurgical and supermicrosurgical anastomoses to harvesting of ALT flaps, but a model of internal mammary vessel dissection currently does not exist. 7,12 The domestic pig is an animal model used frequently in medical research for its anatomic and metabolic similarity to humans. [13][14][15][16][17] As a preclinical model, the importance of the domestic pig cannot be overstated.…”
Section: Discussionmentioning
confidence: 99%
“…11 Innovative training models have been created in many areas of microsurgery from microsurgical and supermicrosurgical anastomoses to harvesting of ALT flaps, but a model of internal mammary vessel dissection currently does not exist. 7,12 The domestic pig is an animal model used frequently in medical research for its anatomic and metabolic similarity to humans. [13][14][15][16][17] As a preclinical model, the importance of the domestic pig cannot be overstated.…”
Section: Discussionmentioning
confidence: 99%
“…The development of manual skills in several fields as general surgery, plastic surgery, urology, gynecology, and orthopedics have been extensively studied. 3,7,[15][16][17] Many theories have been formulated to understand the learning of manual skills and the development of surgical skills. Among learning models, one of the most effective has been described as "deliberate practice," where the individual must focus on a specific and defined task (usually identified by the tutor), which is repeated multiple times with continuous feedback by the trainer/tutor.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of the animal models are ethical or infectious problems (such as Q fever in sheep), especially when live animals are used, as reported also by Costa. 7 Those problems can be overcome by the use of ex vivo animal specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The type of training models continues to grow, with the first description of a nonliving biological simulation using chicken legs for anterolateral thigh flap training. 17 For institutions that lack the available of dry and animal laboratory resources, alternative options exist. A randomized controlled trial based in London showed that training using either a jeweler's microscope or iPad produced comparable results to laboratory-based training.…”
Section: Discussionmentioning
confidence: 99%